Viral meningoencephalitis complicated with cerebral edema and coma: efficacy of complex therapy with l-lysin escinate - N. V. Skripchenko; A. A. Vilnitz; E. Y. Gorelik; N. F. Pulman; A. I. Konev; E. Yu. Skripchenko (Вестник анестезиологии и реаниматологии)
The article presents a clinical case of a 14-year-old patient with viral meningoencephalitis complicated with cerebral edema and a brain coma caused by herpes simplex viruses. Comprehensive etiopathogenetic therapy was not sufficiently effective due to the late referral for medical help and the late start of treatment. It has been shown that the use of the L-lysine escinate preparation up to 10 intravenous injections in a single dose of 0.15 mg/kg twice a day, even in the later stages of encephalitis, which has an extremely severe course due to cerebral edema development, is highly effective due to its multifactorial actions.